2019
DOI: 10.3390/geriatrics4040061
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and Expectations on Antibiotic Use among Older Adults in Malaysia: A Cross-Sectional Survey

Abstract: Antibiotics are commonly prescribed among older adults, and inappropriate use of antibiotics has been noted. However, there is limited information about their knowledge and expectations for antibiotics. This study aimed to assess older adults' knowledge of antibiotic use and resistance, their expectations for antibiotics and the relationship between knowledge, expectation and inappropriate practices related to antibiotic use. A cross-sectional survey involving respondents aged 60 years and above was conducted,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 50 publications
(94 reference statements)
3
20
2
1
Order By: Relevance
“…This is consistent with data from other LMIC community settings as well as formal primary care and informal/private healthcare provider settings in both LMICs and high income countries (HICs) [13,[41][42][43][44][45][46][47][48]. Evidence from both LMICs and HICs shows how important patients' and caregivers' beliefs, expectations and demands are in determining whether healthcare providers prescribe/sell antibiotics inappropriately, which highlights that the public have a vital role to play in tackling inappropriate antibiotic use among humans [48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 70%
“…This is consistent with data from other LMIC community settings as well as formal primary care and informal/private healthcare provider settings in both LMICs and high income countries (HICs) [13,[41][42][43][44][45][46][47][48]. Evidence from both LMICs and HICs shows how important patients' and caregivers' beliefs, expectations and demands are in determining whether healthcare providers prescribe/sell antibiotics inappropriately, which highlights that the public have a vital role to play in tackling inappropriate antibiotic use among humans [48][49][50][51][52].…”
Section: Discussionsupporting
confidence: 70%
“…The overall prevalence of antibiotic consumption in older people from 2006 to 2017 in Spain was 4.94%. This percentage was lower compared to previous studies conducted among the non-institutionalized elderly population, which ranged from 11% to 45%, with a significant rise over the past decade [23,[33][34][35][36]. The variation observed may be due to multiple factors, rather than differences in health-care systems, including the number of general practitioners in a country, antibiotic dose regimens, guidelines, patients' expectations and the attitude towards taking medication, cultural and social factors, as well as the source of information available to the general practitioners [37].…”
Section: Discussioncontrasting
confidence: 70%
“…(4) Malaysia in an upper-middle income country and research has shown that major contributing factors towards ABR in this country are also contributed by overuse and misuse of antibiotics. (5) But the situation of ABR in this country is unique compared to other LMIC. Over the years the country has manage to sustain a government-led publicly funded health care system that is committed to achieve universal health coverage (UHC).…”
Section: Introductionmentioning
confidence: 91%
“…Furthermore, previous research on antibiotic knowledge and attitude especially among the local population are congregated among hospital-based patients. (5,12,13). Therefore, the aim of this study is to (i) determine the community's attitude towards antibiotic usage, (ii) their antibiotic knowledge, (iii) the correlation between antibiotic knowledge and their attitude towards antibiotic and (iv) factors associated with inappropriate attitude towards antibiotic usage among patients attending a public primary care clinic.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation